Analisis Potensi Objek Wisata Pemandian Air Panas Kabupaten Halmahera Utara : Studi Kasus Desa Mamuya Kecamatan Galela - Soamole, Bakri; muhammad, musdar; Talib, Bahrun; Tari, Hasnia (Jurnal Bingkai Ekonomi (JBE), 2024)
The research method uses descriptive quantitative methods. Data analysis techniques using SWOT analysis. The results of the study; the strengths of the potential tourist attraction of hot springs in Mamuya village, Galela sub-district, North Halmahera district are high. In this aspect of strength, beautiful, cool and pristine natural panoramas. Good security conditions. The atmosphere of tourist attractions that provide comfort occupies a high category and the direction of travel of tourist attractions that are still close to settlements